The Moderation Effects of Comparative Thinking Between Gratitude and Negative Affect During the COVID-19 Outbreak - Bernabe-Valero, Gloria; Blasco-Magraner, José Salvador; Aguilar-Moya, Remedios; Moret-Tatay, Carmen (Frontiers in Psychology, 2021)
The aim of this research is to examine the role of Covid-19 perceptions on gratitude and emotional affect. To this propose, a mediation analysis was conducted. Age and sex are also addressed as variable of interest as described in previous literature. A total of 306 north Americans fulfilled the questionnaire, based on emotion self-perception during Covid-19 outbreak, PANAS for positive and negative affect, as well as GQ-6 scores for gratitude. The main results of the current study related to the Covid-19 outbreak can be listed as follows: i) A mediation effect was found for negative effect but not for positive affect; ii) Age did not predict Gratitude, iii) Gender differences were found on Gratitude. These results might be of interest for training programs in an applied levels and theoretical models of gratitude.